(untitled) (The International Research Journal of Management Science, 2022)
AbstractThe purpose of this study was to examine the vulnerability caused by the COVID-19 pandemic on the overall operationsand profitability of star hotels in Nepal and to explore their survival strategies. This study used both qualitative and quantitative approaches based on descriptive research design. The required primary data were collected through questionnaires and interviews with the hotel operators and managers, while the secondary data was from annual reports of sample hotels. For the analysis of qualitative information, thematic analysis was used based on grounded theory. Descriptive statistics were used for analyzing the secondary data. Results revealed an intensely negative effect of the pandemic on one-star and two-star hotels, followed by three-star, four-star, and five-star hotels, respectively. Operations were badly affected, and hence the net profits decreased;the cost of inbound materials increased significantly along with their unavailability. Hotels followed the diversification strategy with cost-focused differentiation. The research identified small but insufficient support from the government for necessaryoperations. This study provides essential insights to the policymakers, hotel entrepreneurs and readers to fulfill the knowledge gap in the field of study in the last section of the paper.